Effects of the rocky substrate properties on distribution of Cyanophyta in supralittoral zone of the sea (CHORNOMORSKI BOTANICAL JOURNAL, 2010)
Rocks are characterized in supralittoral zone of the Crimean coast of the Black and Azov Seas. The article presents data on the species list of Cyanophyta in various supralittoral rocky substrates.
Keywords: Cyanophyta, species diversity, Black Sea, Azov Sea, rocky substrate, rocks.